EFEITO DA ARMADILHA LUMINOSA SÔBRE INFESTAÇÃO DE Grapholita molesta (BUSCK) EM MACIEIRA - Silveira Neto, Sinval; Carvalho, Ricardo Pereira Lima; Camargo, Ari Hoffmann de; Rossetto, Carlos Jorge (REVISTA DE AGRICULTURA, 2016)
EFEITO DA ARMADILHA LUMINOSA SÔBRE INFESTAÇÃO DE Grapholita molesta (BUSCK) EM MACIEIRA